Aesthetics of sorrow : the wailing culture of yemenite-jewish women - Gamliʼel, Ṭovah, 1965- (Raphael Patai series in Jewish folklore and anthropology., 2014)
Decodes the cultural and psychological meanings of the "wailing culture" following the death of a member of the Yemenite Jewish community, based on anthropological research among Yemenite Jewish communities in Israel in 2001-2003